THE EFFECT OF VIRTUAL LABORATORY IMPLEMENTATION ON THE SCIENCE LITERACY ABILITY OF CLASS VIII STUDENTS ON MATERIAL FORCE AND MOVEMENT OF OBJECTS AT MTS NEGERI 1 JEMBER - Cincin Nohan Rembulan; Laily Yunita Susanti (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
Students who do not raise questions that are applicable and the ability to identify a problem according to the concept of science, show that the scientific literacy of students is classified as low science in a real context. In general, this study aims to examine the effect of the application of the virtual laboratory on the scientific literacy ability of students on the subject matter of force and motion. This research method uses quantitative research types Quasi Experimental Design. The population in this study were students of class VIII and the sample was selected by purposive sampling. The instrument of scientific literacy is a description test. Prerequisite test results use Kolmogorov Smirnov for normality and use One-Way ANOVA for homogeneity. Then the hypothesis test was performed using the Z test. The results of the study obtained an average value of scientific literacy at a pretest significance value of 0.403> 0.05 so that H0 was accepted and Ha was rejected. While the posttest value has a significance value of 0.001 <0.005 so that H0 is rejected and Ha is accepted. So that it shows a significant influence between the scientific literacy abilities of students in the two classes.